2018
DOI: 10.1111/papr.12686
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid and Cortisol Serum Levels Following Intra‐articular Triamcinolone Acetonide Lumbar Facet Joint Injections

Abstract: The peak serum concentration of triamcinolone following intra-articular facet joint injections occurred within 24 hours. The median terminal elimination half-life was 213 hours, but baseline cortisol levels were suppressed for an average of 4.4 days. Clinically, the prolonged half-life and endocrine effects of triamcinolone could increase the risk for serious drug-drug interactions in patients taking medications that inhibit corticosteroid metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…In the review, it is suggested that the effect is maximal after 48 h and lasting for 1–4 weeks. This transient effect of CSI on serum levels is further shown by several studies (Armstrong, English, Gibson, Chakraborty, & Marks, 1981; Derendorf, Möllmann, Grüner, Haack, & Gyselby, 1986; Dickson, Reid, Nicholson, Lamer, & Hooten, 2018; G. Habib, Jabbour, Artul, & Hakim, 2014; Mader, Lavi, & Luboshitzky, 2005; Reeback, Chakraborty, English, Gibson, & Marks, 1980; Weitoft & Rönnblom, 2006). However, the Broerson meta‐analysis did show that there was adrenal insufficiency in patients post CSI (Broersen, Pereira, Jørgensen, & Dekkers, 2015).…”
Section: Introductionsupporting
confidence: 56%
“…In the review, it is suggested that the effect is maximal after 48 h and lasting for 1–4 weeks. This transient effect of CSI on serum levels is further shown by several studies (Armstrong, English, Gibson, Chakraborty, & Marks, 1981; Derendorf, Möllmann, Grüner, Haack, & Gyselby, 1986; Dickson, Reid, Nicholson, Lamer, & Hooten, 2018; G. Habib, Jabbour, Artul, & Hakim, 2014; Mader, Lavi, & Luboshitzky, 2005; Reeback, Chakraborty, English, Gibson, & Marks, 1980; Weitoft & Rönnblom, 2006). However, the Broerson meta‐analysis did show that there was adrenal insufficiency in patients post CSI (Broersen, Pereira, Jørgensen, & Dekkers, 2015).…”
Section: Introductionsupporting
confidence: 56%
“…Betamethasone is more soluble than triamcinolone and HPA suppression is seen at doses of 6 mg [ 24 ]. Dickson et al studied facet joint corticosteroid injections with triamcinolone acetonide 40 mg and found that HPA suppression occurs for an average of 4.4 days [ 11 ]. The depressed HPA-axis is of concern in the setting of the COVID-19 pandemic because if a patient were to encounter a stressful event such as a severe infection, s/he may not be able to mount a sufficient stress response to appropriately fight the infection, and a depressed HPA-axis is known to correlate with poor outcomes in critically ill persons [ 8 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroid (betamethasone sodium phosphate and acetate injectable suspension (6 mg/mL, American Regent Inc., Shirley, NY; dose 6–21 mg), triamcinolone acetonide injectable suspension (40 mg/mL, Bristol Myers Squibb Company, New York, NY; dose 40–80 mg), methylprednisolone acetate (40 mg/mL, Pfizer, New York, NY; dose 60 mg), or dexamethasone (4 mg/mL, Fresenius Kabi, Lake Zurich, IL; dose 10 mg) with or without anesthetic (lidocaine 1% (AuroMedics Pharma LLC, E. Windsor, NJ; 1–4 mL) or ropivacaine 0.2% (AuroMedics Pharma LLC, E. Windsor, NJ; 1–5 mL)) or bupivacaine 0.5% (Hospira, Inc, Lake Forest, IL; 2–4 mL) was then injected. Following the injection, the patient was instructed to physically distance for 1–2 weeks, based on the possibility of suppression of the immune system and HPA-axis [ 10 , 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Intra-articular triamcinolone is absorbed into soft tissues over a time course of 2 to 3 weeks. Its effect on adrenal suppression is dose-dependent, with the maximum effect after intra-articular administration observed when levels are greater than 1.9 ng/mL (11). ICS following triamcinolone injections even in the absence of CYP3A4 inhibition has been reported (12).…”
Section: Discussionmentioning
confidence: 99%